2016
DOI: 10.3389/fpubh.2016.00131
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Influence of Dam Methylation on Gene Expression and Attachment in Uropathogenic Escherichia coli

Abstract: Urinary tract infections (UTI) are among the most frequently encountered infections in clinical practice globally. Predominantly a burden among female adults and infants, UTIs primarily caused by uropathogenic Escherichia coli (UPEC) results in high morbidity and fiscal health strains. During pathogenesis, colonization of the urinary tract via fimbrial adhesion to mucosal cells is the most critical point in infection and has been linked to DNA methylation. Furthermore, with continuous exposure to antibiotics a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 99 publications
2
13
0
Order By: Relevance
“…Here we have shown that the loss of dam results in a significantly decreased mean generation time and that its absence contributes to differences in the ABR profile compared to a wild-type parental strain and confers a measure of resistance to the antimicrobial TCS. The increased generation time (Table 2) seen with the dam knockout matches observations of damdeficient strains of uropathogenic E. coli [34]. This increase is likely a consequence of the role of dam in replication [32,34].…”
Section: Discussionsupporting
confidence: 68%
“…Here we have shown that the loss of dam results in a significantly decreased mean generation time and that its absence contributes to differences in the ABR profile compared to a wild-type parental strain and confers a measure of resistance to the antimicrobial TCS. The increased generation time (Table 2) seen with the dam knockout matches observations of damdeficient strains of uropathogenic E. coli [34]. This increase is likely a consequence of the role of dam in replication [32,34].…”
Section: Discussionsupporting
confidence: 68%
“…In other bacteria, hypomethylation has been attributed to transcription factors occluding MTase access to DNA when their respective target motifs overlap (Beaulaurier et al; Hernday et al, 2002 ; Stephenson and Brown, 2016 ). To determine if this may be the case in M. tuberculosis , we scanned the context sequence of each consistently hypomethylated site for TFBS motifs previously characterized in M. tuberculosis ( Minch et al, 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…In M. tuberculosis , MamA-mediated transcriptional regulation has been demonstrated at four promoters in M. tuberculosis ( Shell et al, 2013 ), presumably through interaction with the −10 promoter element. A second characterized mechanism of DNA methylation mediated cis-regulation is interaction between methylated bases, MTases, and transcription factors ( Beaulaurier et al, 2015 ; Hernday et al, 2002 ; Stephenson and Brown, 2016 ), which has been hypothesized to occur at specific sites in M. tuberculosis ( Phelan et al, 2018 ; Zhu et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Dam, DNA adenine methylase, plays important role in DNA replication, DNA mismatch repair and SOS response (a genome-wide response to DNA damage where cell cycle is arrested and DNA repair and mutagenesis is active; Stephenson and Brown, 2016 ). Dam plays a protective role during oxidative stress in S .…”
Section: Resultsmentioning
confidence: 99%